Millimeter-Wave Radars for Environmental Studies - Vavriv, D.M.; Volkov, V.A.; Bormotov, V.N.; Vynogradov, V.V.; Kozhyn, R.V.; Trush, B.V.; Belikov, A.A.; Semenyuta, V.Ye. (Радиофизика и радиоастрономия, 2002)
A review is given of recent activities undertaken in the Institute of Radio Astronomy of the National Academy of Sciences of Ukraine for the development of millimeter-wave radars. The radars constructed include cloud radars and a side-looking airborne radar system. They are capable to perform real-time, high-resolution measurements in the frequency bands of 36 and 95 GHz. The setup of these instruments, the novel technical solutions, and the signal processing technique introduced are discussed. The results obtained with such instruments during measurement campaigns are presented as well.